Valor de mercado de acesso a eletricidade, água, esgoto, gás e telefonia fixa - Sergei Suarez Dillon Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– Owner-occupied housing and public infrastructure services are a relevant part of the income distribution whose impacts have not yet been adequately studied, at least not from the distributive point of view. This paper suggests a way to find the market value for these services using hedonic prices. While far from new, this methodology is nevertheless useful in assigning values to these services. The paper uses Brazilian data from 1995, 2004, and 2014 to impute rental values for owner occupied housing and the associated infrastructure services. The results are that imputation of housing services considerably reduces inequality and that public infrastructure services have become more progressive as their expansion brings these services to increasingly poorer households.
Keywords: D31; 330; hedonic prices; public infrastructure services; imputed rent; income distribution